Digital Marketing Training to Increase Community Agricultural Products Sales Volume Nglarangan Village - Manan, Moh. Abdul; Sudiyanto, Sudiyanto; Rejekiningsih, Triana (Universitas Sebelas Maret, 2023)
The development of digital technology has significantly changed the way business is done, including in the field of marketing. Digital marketing is increasingly crucial for communities to achieve their business goals in this digital era. This study aims to explore the effectiveness of digital mark eting training in increasing sales of agricultural products in Nglarangan Village. In a modern era dominated by digital technology, digital marketing training emerges as an effective solution to expand mark ets and increase sales of agricultural products locally. The research method involves delivering digital mark eting training to the Nglarangan Village community, including farmers, local businesses, and individuals involved in the production of agricultural products. The training will cover a basic understanding of digital technology, social media utilization, the creation of engaging content, and the management of e-commerce platforms. This research uses qualitative methods by applying interviews and participatory observation. The data collected will be thematically analyzed to identify patterns and findings during and after the training. A pre- and post-training sales evaluation will be conducted to understand the impact on business success and increased sales. The results of this study are expected to increase understanding of the effectiveness of digital mark eting training in the context of local agriculture. An important implication of this research is to provide guidance to the government and related parties in developing digital marketing training programs that suit the needs of Nglarangan Village and improve the community's skills and knowledge in digital marketing as well as the sales volume of their agricultural products.